2013
DOI: 10.1016/j.fgb.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cis-acting factor modulating the transcription of FUM1, a key fumonisin-biosynthetic gene in the fungal maize pathogen Fusarium verticillioides

Abstract: Fumonisins, toxic secondary metabolites produced by some Fusarium spp. and Aspergillus niger, have strong agro-economic and health impacts. The genes needed for their biosynthesis, named FUM, are clustered and co-expressed in fumonisin producers. In eukaryotes, coordination of transcription can be attained through shared transcription factors, whose specificity relies on the recognition of cis-regulatory elements on target promoters. A bioinformatic analysis on FUM promoters in the maize pathogens Fusarium ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…A cluster of 17 fumonisin biosynthetic genes ( FUM ) have been identified and characterized in Fusarium verticillioides ; these co-expressed genes include a gene encoding polyketide synthase (PKS), two genes encoding fatty acid synthases, nine genes encoding cytochrome P450 monooxygenases, dehydrogenases, transporter proteins, an aminotransferase, and a dioxygenase [17,18,19]. FUM1p was identified as the key enzyme of fumonisin biosynthesis, and the cluster-specific Zn(II)2Cys6 transcription factor (TF) Fum21p was found along with a putative TF-binding motif (CGGMTA) to participate in transcriptional activation of FUM1 [17,20,21,22,23]. The FUM19 gene is located approximately 35 kb downstream from the FUM1 gene and encodes an ABC (ATP-binding cassette) transporter involved in extracellular export of fumonisins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cluster of 17 fumonisin biosynthetic genes ( FUM ) have been identified and characterized in Fusarium verticillioides ; these co-expressed genes include a gene encoding polyketide synthase (PKS), two genes encoding fatty acid synthases, nine genes encoding cytochrome P450 monooxygenases, dehydrogenases, transporter proteins, an aminotransferase, and a dioxygenase [17,18,19]. FUM1p was identified as the key enzyme of fumonisin biosynthesis, and the cluster-specific Zn(II)2Cys6 transcription factor (TF) Fum21p was found along with a putative TF-binding motif (CGGMTA) to participate in transcriptional activation of FUM1 [17,20,21,22,23]. The FUM19 gene is located approximately 35 kb downstream from the FUM1 gene and encodes an ABC (ATP-binding cassette) transporter involved in extracellular export of fumonisins.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies of fumonisin were performed in F. verticillioides [21,32,33] and are related to the function of fumonisin synthesis genes [27,34], methods of detection of fumonisin [35,36,37], and the regulation of fumonisin synthesis factors [38,39,40,41]. However, there are few studies of fumonisin production in F. proliferatum .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several genes that regulate pathogenesis and/or fumonisin biosynthesis in F. verticillioides have been identified that do not reside in the FUM cluster, including the zinc-finger transcription factor ZFR1 (Flaherty and Woloshuk, 2004), components of monomeric and heterotrimeric G-protein signalling such as GBP1 and GBB1 (Sagaram et al, 2006;Sagaram and Shim, 2007), map kinase-associated signalling (Zhang et al, 2011) and components of the mediator complex (FCC1 and FCK1) associated with RNA polymerase (Shim and Woloshuk, 2001;Bluhm and Woloshuk, 2006). Recently, histone acetylation and a novel cis-acting element in the FUM cluster were identified as key regulatory factors in the expression of fumonisin biosynthetic genes (Visentin et al, 2012;Montis et al, 2013). The reduction in fumonisin accumulation in kernels colonized by the Δubl1 mutants appeared to be a direct outcome of reduced kernel colonization, and thus no evidence exists for a direct link between the N-end rule pathway and the regulation of fumonisin.…”
Section: Discussionmentioning
confidence: 99%
“…in the analysed pea seeds suggests the possibility of contamination with mycotoxins, as both F. proliferatum and F. verticillioides have the ability to produce fumonisins. Fumonisin biosynthesis is determined by the activity of the FUM gene cluster comprising of 17 FUM genes (30,31) and numerous studies have shown that the sequence analysis of FUM1 gene may be successfully used to identify Fusarium strains (32)(33)(34)(35). An analysis of the genetic divergences of this particular gene among the peaderived strains and the strains originating from different host species has shown a higher level of similarity between the strains of F. proliferatum …”
Section: Figure 1b Level Of Fungal Contamination [In % Of Contaminatementioning
confidence: 99%